2021
DOI: 10.1111/jpn.13599
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lipid deposition of intramuscular preadipocytes in Tan sheep co‐cultured with satellite cells or alone

Abstract: The purpose of this study was to investigate the effect of the skeletal muscle satellite cells (SMSCs) on the lipid deposition of the intramuscular preadipocytes (IMPs) in a co‐culture system of the Tan sheep cells. The SMSCs and IMPs from Tan sheep were separated and cultured. After the two kinds of cells were separated and cultured, they were inoculated onto a transwell cell chamber co‐culture plate for co‐cultivation. When the cell density reached more than 90%, the cells were induced to differentiate. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Similarly, as milk-producing ruminants, goats and sheep are also regulated by PPARγ. Many studies indicate that PPARγ is involved in adipocyte differentiation and adipogenesis in sheep/goats [59][60][61][62][63], though, in addition to fat regulation, PPARγ was previously thought to be involved in the regulation of hormones in goats and sheep [64,65]. However, there has been some relevant research in recent years.…”
Section: Pparγmentioning
confidence: 99%
“…Similarly, as milk-producing ruminants, goats and sheep are also regulated by PPARγ. Many studies indicate that PPARγ is involved in adipocyte differentiation and adipogenesis in sheep/goats [59][60][61][62][63], though, in addition to fat regulation, PPARγ was previously thought to be involved in the regulation of hormones in goats and sheep [64,65]. However, there has been some relevant research in recent years.…”
Section: Pparγmentioning
confidence: 99%
“…On the other hand, the results of a study done by Chu et al have shown that during cocultivation C2C12 cells inhibit the proliferation and differentiation of 3T3-L1 pre-adipocytes by suppressing glucocorticoid receptor (GR) gene expression [139]. A recently published study with Tan sheep cells showed a decrease in the number of lipid droplets in the intramuscular preadipocytes (IMPs) that were in a co-culture system with skeletal muscle SCs [140].…”
Section: Myoblasts and Adipocytes Co-cultivationmentioning
confidence: 99%